2010
DOI: 10.1007/s10212-010-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

The perception of workload and task complexity and its influence on students’ approaches to learning: a study in higher education

Abstract: Researchers have tried to induce a deeper approach to learning by means of student-centred learning environments. Findings did not always confirm the positive hypotheses. This has given rise to the question as to what the discouraging or encouraging factors are for inducing a deep approach to learning. The aim of this research study is to determine whether perceived workload and task complexity are discouraging or encouraging factors. In addition, these relationships will be investigated under different induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 49 publications
1
34
0
8
Order By: Relevance
“…Kyndt et al (2011a) noted that the efforts made to induce meaningful learning by means of student-centred learning environments, such as PBL and student-activating teaching methods produced mixed results. Although several studies confirm that such environments have a positive influence on learning quality, surprisingly, other studies have observed the opposite effects and in many cases results have shown increases in surface approaches (evidence can be found in Gijbels et al, 2005;Nijhuis et al, 2005;Segers et al, 2006or Struyven et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Kyndt et al (2011a) noted that the efforts made to induce meaningful learning by means of student-centred learning environments, such as PBL and student-activating teaching methods produced mixed results. Although several studies confirm that such environments have a positive influence on learning quality, surprisingly, other studies have observed the opposite effects and in many cases results have shown increases in surface approaches (evidence can be found in Gijbels et al, 2005;Nijhuis et al, 2005;Segers et al, 2006or Struyven et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is doubtful if the students with this profile develop a reflected expertise and a deep learning approach (Janssen, 1996). Alternatively, it might very well be the case that for this group, which comes with rather high prior knowledge, the course does not offer enough of a challenge to engage in deeper learning activities (Kyndt, Dochy, Struyven, & Cascallar, 2011).…”
Section: Interpretation and Conclusionmentioning
confidence: 98%
“…Literature suggests that an instructor or course that encourages a surface approach to learning, yields perceptions of a heavier workload, whether or not it is 'heavier'. Kyndt et al found no significant relationship between perceived workload and students' approaches to learning, but found a perceived lack of information "consistently increases students' surface approaches to learning regardless of the induced workload and task complexity" [9]. This suggests that student expectations, a consequence of available information, can influence perceptions of workload and motivation.…”
Section: Introductionmentioning
confidence: 94%